Estudo de alterações na cavidade oral em pacientes com doença do refluxo gastroesofágico - Correa, Maria Carolina Canteras Scarillo Falotico (2008)
Background - The gastroesophageal reflux disease, which has become highly and increasingly incident, may be manifested by typical (pyrosis and regurgitation) and atypical (pulmonary, otorhinolaryngological and buccal) symptoms. Aim - To analyze alterations in the oral cavity patients with gastroesophageal reflux disease. Methods - One hundred patients were studied being 50 gastroesophageal reflux disease patients (group 1) and 50 controls (group 2). All patients were submitted to an oral clinical exam and specific survey. Patients in group 1 were submitted to upper endoscopy, manometry and esophageal pH monitoring. Results - The upper endoscopy revealed esophagitis in all patients, 20 erosive esophagitis, 30 no-erosive esophagitis and 38 hiatal hernia. Average pressure of the lower esophageal sphincter was 11 ± 4,8 mm Hg and of the upper esophageal sphincter 75 ± 26,5 mm Hg. In 42 patients of group 1 (84%) pathological gastroesophageal reflux was observed. Clinical exams revealed: dental erosions in group 1: 273 faces and in group 2: 5 tooth decays in group 1: 23 and 115 in group 2; abrasion in group 1: 58 and in group 2: 95; attrition wear: 408 in group 1 and 224 in group 2. The most damages was the palatine face. In group 1, 21 patients complained about frequent episodes of cankers sores, 35 of tooth sensibility, 26 of burning mouth and 42 of sour taste in the mouth. In group 2 the complaints were observed in lower number of patients. Conclusions - Patients with gastroesophageal reflux disease present higher incidence of dental erosion, cankers sores, mouth burning sensation, sensitivity and sour taste than controls. Patients with gastroesophageal reflux disease show lower incidence of tooth decays as compared to controls.